Nurses' preparedness, readiness, and anxiety in managing COVID-19 pandemic - Chua, Bee Seok; Getrude Cosmas; Norkiah Arsat (SAGE Publications, 2021)
Nurses’ preparedness has been very important for them to treat patients effectively during the COVID-19 pandemic and serve the community. Nurses provide a vital role in mitigating the effects of health crises. In order to help nurses better understand their skills, abilities, and knowledge, as well as the actions that they should take to manage care, the research aims of this study are to (1) investigate the level of preparedness, readiness, and anxiety among nurses during the COVID-19 outbreak in Sabah, Malaysia; (2) examine the effects of various differences in preparedness and readiness among nurses; and (3) examine the effect of COVID-19 preparedness on anxiety among nurses. The results revealed that the nurses were moderately competent in managing the COVID-19 care situation. Each of the 3 differentiating characteristics (age, work experience, and previous disaster experience) did not predict how nurses would manage COVID-19 preparedness significantly. Besides, we also found only 2 dimensions of preparedness (familiarity with epidemiology and surveillance and familiarity with psychological issues) significantly predicted nurses’ anxiety levels. Familiarity with epidemiology and surveillance predicted nurses’ anxiety positively; in contrast, familiarity with psychological issues negatively influenced nurses’ anxiety.